AZERBAIJAN FINANCIAL AND BANKING SYSTEM DURING THE GLOBAL CRISIS: SHIFT OF EMPHASIS IN INTERNATIONAL COMPARATIVE ASSESSMENTS - HAJIYEV, Shamseddin; MURSHUDLI, Fakhri (CENTRAL ASIA AND THE CAUCASUS, 2009)
The creation of a robust, innovative financial and banking system capable of meeting the needs of society is among the strategic tasks of the republic’s economic policy aimed at ensuring the national sovereignty of this system as the country integrates into the global market. A sound financial system and increasing competitiveness of the banking sector are effective factors of sustainable economic growth making it possible to survive the global financial and economic collapse with relatively insignificant losses. International comparative assessments are among the main instruments for analyzing the financial and credit strength and vulnerability of individual countries. At the same time, the realities of the global crisis show that the techniques, principles, emphasis and focus of these assessments in current conditions should change radically. Otherwise, their objectivity and validity will be called into question, and this will in turn have a negative impact on the decision-making process.